2017
DOI: 10.1159/000475460
|View full text |Cite
|
Sign up to set email alerts
|

Administration of the Mitochondrial Permeability Transition Pore Inhibitor, TRO40303, prior to Primary Percutaneous Coronary Intervention, Does Not Affect the Levels of Pro-Inflammatory Cytokines or Acute-Phase Proteins

Abstract: Objectives: In the MITOCARE study, reperfusion injury was not prevented after administration of the mitochondrial permeability transition pore (mPTP) opening inhibitor, TRO40303, in patients with ST-segment elevation myocardial infarction (STEMI) treated with primary percutaneous coronary intervention (pPCI). The effects of TRO40303 on pro-inflammatory cytokines and acute-phase proteins were assessed. Methods: STEMI patients (n = 163, mean age 62 years) with chest pain within 6 h before admission for pPCI were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 52 publications
0
3
0
Order By: Relevance
“…We have previously shown that there were no statistically significant treatment effects of TRO40303 on the levels of PTX3, IL-6 or hs-CRP during the first 72 hours after primary PCI 16 (online Appendix Table 2). Therefore, the kinetics of PTX3, IL-6 and hs-CRP were analysed in all 161 patients.…”
Section: Blood Sampling and Analysesmentioning
confidence: 97%
“…We have previously shown that there were no statistically significant treatment effects of TRO40303 on the levels of PTX3, IL-6 or hs-CRP during the first 72 hours after primary PCI 16 (online Appendix Table 2). Therefore, the kinetics of PTX3, IL-6 and hs-CRP were analysed in all 161 patients.…”
Section: Blood Sampling and Analysesmentioning
confidence: 97%
“…The MITOCARE study demonstrated no effect of TRO400303 in limiting myocardial injury following reperfusion between treatment and placebo [125] or effecting pro-inflammatory cytokines at 72 hours following PCI [126].…”
Section: The Disappointment Of Tro40303mentioning
confidence: 97%
“…Most of these compounds must yet undergo proof-of-concept trials and have their safety and clinical effectiveness to be scrutinized. The once-promising compound TRO40303, however, has performed poorly in more than one translational study [321,322], with its clinical relevance regarding the reduction of IRI due to percutaneous coronary intervention for acute myocardial infarction. It is worth mentioning that hydroxytyrosol, a phenolic compound found in olive oil, provided significant protection to the myocardium against IRI, by inhibiting mPTP opening although it is still unclear whether or not this effect is CyD-dependent [323].…”
Section: Therapeutics: the Pharmacological Approachmentioning
confidence: 99%